To pediatrician about feverish conditions in children: what to know and know how - I. N. Zakharova; A. L. Zaplatnikov; T. M. Tvorogova; E. B. Machneva (Медицинский совет, 2016)
Fever is one of the most common nonspecific reactions to various pathological processes in children. The article tells about the specifics of thermoregulation processes, etiology and pathogenesis of fever in children, mechanisms of action of antipyretics. The focus is on age peculiarities of thermoregulatory mechanisms, as well as differential diagnosis of fever based on the etiological factor. The article also emphasizes the importance of adequate choice of antipyretic drugs for children.